2015
DOI: 10.1111/bdi.12333
|View full text |Cite
|
Sign up to set email alerts
|

Auditory processing deficits in bipolar disorder with and without a history of psychotic features

Abstract: Our findings suggested that, although deficits in frequency discrimination and emotion recognition are more severe in SZ, these impairments extend to BD+. Although our results did not support the idea that auditory hallucinations may be related to these deficits, they indicated that basic auditory deficits may be a marker for psychosis, regardless of SZ or BD diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 86 publications
2
12
0
Order By: Relevance
“…Abnormalities in CNS myelin are found in multiple psychiatric disorders including schizophrenia, bipolar disorder, and chronic depression (Fields, ), and these conditions are linked to deficits in auditory sensory processing (Kahkonen et al, ; McLachlan et al, ; Zenisek et al, ). One link between abnormal myelin and auditory dysfunction in mental illness is the pathophysiology of auditory verbal hallucinations (AVH), which is a common symptom of psychiatric illness.…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…Abnormalities in CNS myelin are found in multiple psychiatric disorders including schizophrenia, bipolar disorder, and chronic depression (Fields, ), and these conditions are linked to deficits in auditory sensory processing (Kahkonen et al, ; McLachlan et al, ; Zenisek et al, ). One link between abnormal myelin and auditory dysfunction in mental illness is the pathophysiology of auditory verbal hallucinations (AVH), which is a common symptom of psychiatric illness.…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…19 Only a few studies have investigated sensory processing in BD; however, Zenisek et al 47 features did not differ significantly from healthy controls, indicating that sensory processing deficits may also be present in BD, but only in those experiencing psychosis. 47 No significant differences were found when BD patients with and without a history of auditory hallucinations were compared; however, these analyses were limited to a sample of 30 patients, and may have been underpowered. Further research is needed to elaborate on the significance of cortical regions involved in sensory processing and auditory hallucinations in BD patients.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, a reduced ability to discriminate between tones has been shown in schizophrenia patients . Only a few studies have investigated sensory processing in BD; however, Zenisek et al compared performance in a tone discrimination task, and found that BD patients with psychotic features performed intermediate to schizophrenia patients and BD patients without psychotic features. BD patients without psychotic features did not differ significantly from healthy controls, indicating that sensory processing deficits may also be present in BD, but only in those experiencing psychosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that sensory integration impairments are linked with mental health concerns of adults (Balliard & Whigham, 2017). For example, deficits in tone recognition have been linked with impairments in emotional identification (Zenisek et al, 2015), and disruptions in late stage visual processing impacts attention, (Jahshan et al, 2014), for adults with bipolar disorder.…”
Section: Patterns Of Sensory Modulation Among Children and Adolescentmentioning
confidence: 99%